Meronimi Mulut - Teodora Nirmala Fau (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2015)
This research aims at discussing about mouth meronymy or what is known as vocabulary which is clustered on mount shaper element. In Indonesian language, there are 25 words which refer to element of mouth, but there are only nine vocabularies that include in direct meronymy of mouth. All of words which can be classified as meronymy of mouth are words whose lexical meanings show their position on epiglottis.